Pembelajaran PIBP dan Signifikansinya dalam Peningkatan Mutu Akademik Mahasiswa - Ahmad Choirul Rofiq (IAIN Ponorogo, 2009)
User education at STAIN (State Islamic College) Ponorogo, known as learning PIBP (Penelusuran Informasi Bahan Pustaka) or the search of information and reference materials, is a purposive effort especially designed to give new students, who basically have many various academic background. knowledge and ability to learn how they can take advantage of provide library services maximally and how they are able to search information in the library quickly and accurately.